Protective Effect of Ischemic Preconditioning on Myocardium Against Remote Tissue Injury Following Transient Focal Cerebral Ischemia in Diabetic Rats - Kumas,Meltem (2017)
Abstract Background: Remote ischemic preconditioning (IPreC) could provide tissue-protective effect at a remote site by anti-inflammatory, neuronal, and humoral signaling pathways. Objectives: The aim of the study was to investigate the possible protective effects of remote IPreC on myocardium after transient middle cerebral artery occlusion (MCAo) in streptozotocin- induced diabetic (STZ) and non-diabetic rats. Methods: 48 male Spraque Dawley rats were divided into eight groups: Sham, STZ, IPreC, MCAo, IPreC+MCAo, STZ+IPreC, STZ+MCAo and STZ+IPreC+MCAo groups. We induced transient MCAo seven days after STZ-induced diabetes, and performed IPreC 72 hours before transient MCAo. Remote myocardial injury was investigated histopathologically. Bax, Bcl2 and caspase-3 protein levels were measured by Western blot analysis. Total antioxidant status (TAS), total oxidant status (TOS) of myocardial tissue were measured by colorimetric assay. Oxidative stress index(OSI) was calculated as TOS-to-TAS ratio. For all statistical analysis, p values < 0.05 were considered significant. Results: We observed serious damage including necrosis, congestion and mononuclear cell infiltration in myocardial tissue of the diabetic and ischemic groups. In these groups TOS and OSI levels were significantly higher; TAS levels were lower than those of IPreC related groups (p < 0.05). IPreC had markedly improved histopathological alterations and increased TAS levels in IPreC+MCAo and STZ+IPreC+MCAo compared to MCAo and STZ+MCAo groups (p < 0.05). In non-diabetic rats, MCAo activated apoptotic cell death via increasing Bax/Bcl2 ratio and caspase-3 levels. IPreC reduced apoptotic cell death by suppressing pro-apoptotic proteins. Diabetes markedly increased apoptotic protein levels and the effect did not reversed by IPreC. Conclusions: We could suggest that IPreC attenuates myocardial injury via ameliorating histological findings, activating antioxidant mechanisms, and inducing antiapoptotic activity in diabetic rats.